Exploring change in networks supporting the deliberate practice of popular musicians. (March 2022) - Längler, Manuel; Brouwer, Jasperina; Timmermans, Anneke; Gruber, Hans
Popular musicians are embedded in dynamic networks supporting their expertise development across different phases. During these phases, network actors support different aspects of deliberate practice in which a musician needs to engage to become an expert. Research in the domain of music is scarce in terms of investigating the change in the supportive networks of deliberate practice over time. Semi-structured interviews with five expert and five intermediate popular musicians were used to explore changes in networks supporting the deliberate practice during their childhood, apprenticeship, and career phases. Egocentric network analysis revealed that networks supporting the deliberate practice of expert musicians are more dynamic and less stable when considering the different phases than the networks of intermediates. In addition, experts are supported by a larger number of network actors during the developmental phases. In both groups, the number of network actors decreased as the musicians progressed through the phases. This decrease was more precipitous between the childhood and apprenticeship phases. Overall, expertise development as a popular musician depends not only on deliberate practice but also on the diversity and change in an adaptive support network from childhood to adulthood.